Variations in char structure and reactivity due to the pyrolysis and in-situ gasification using Shengli brown coal - Xu, X.; Wang, Y.; Chen, Z.; Chen, X.; Zhang, H.; Bai, L.; Zhang, Shu (Elsevier, 2015)
© 2015 Elsevier B.V. All rights reserved. The initial reacting environment (such as temperature) could be highly important for determining the properties of char that is formed almost instantly when coal is fed into a hot gasifier. To fundamentally examine this issue, a new two-stage quartz reactor was specially designed, in which the heat treatment for the initial decomposition of Chinese Shengli brown coal particles could be separately and flexibly controlled. The chars generated from coal decomposition at the first stage were either taken out for analysis, or directly entered the second stage of reactor for in-situ gasification in steam. The results indicate that the change in initial heating conditions could impact the char reactivity in both steam and air. Particularly, 600 °C during the pyrolysis stage was a critical point for determining the subsequent char reactivity, especially in air. The porous structure of chars produced from the first stage of reactor was largely dependent on the treating temperature, the variation of which was diminished during the following second stage reaction in steam. The effects of temperature and holding time on carbon structure of chars at the first stage were tremendous. The difference in carbon structure (i.e., ratio of small to large aromatic ring systems) resulted from the pyrolysis was important for its reactivity in the following char-steam and char-oxygen reactions. Besides, the reaction mechanism of the preferential consumption of small aromatic ring systems during char-steam gasification may not always be the same as what the literatures have suggested, but is very much dependent on the nature of char.